The Efforts of Islamic Criminal Law Integration into Indonesian Law Procedures - Arifin, Muhammad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
In recent years, there have been widespread criminal cases with enormous intensity. With a variety of modus operandi, criminal cases both committed by individuals and collectives, are carried out by ordinary people to the executive, legislative and also the judiciary. The cases that most render the sense of justice ripped apart are the many cases of corruption, bribery and collusion. The judiciary that is trusted often betrays a sense of justice by only giving very light laws for cases of corruption and bribery which are detrimental to the country's finances. Therefore many people, especially Muslims, want the application of Islamic law in the criminal field. With strict legal sanctions and supported by sources that originate from the Qur’an, it is hoped that the existing crime can be minimized.